Application of geo-informatics technology to study vegetation index and humidity: A case study of drought in the special economic Eastern region of Thailand - Pholgerddee, P. (International Journal of Agricultural Technology, 2020)
Result showed the different changes in vegetation indicating the spatial-temporal pattern of drought. These factors represented the plant index (NDVI), humidity difference index (NDWI), and plant image index (EVI) values of spatial-temporal pattern image that being high values. It referred to the different areas among various vegetation covering. The NDVI and EVI showed a greater degree of NDWI that provided the difference in combination of vegetation covering and water contents. Finally, the map of severity for classifying the drought in the spatial-temporal pattern was performed. The spatial-temporal pattern of drought can be implied from the NDVI NDWI and EVI instead of using the meteorological data in case of inadequate coverage of climatic data.